To find the slope of the line that passes through the points \((-5, 6)\) and \((-9, -6)\), we can use the formula for the slope \(m\), which is given by:
\[ m = \frac{y_2 - y_1}{x_2 - x_1} \]
Here, \((x_1, y_1) = (-5, 6)\) and \((x_2, y_2) = (-9, -6)\). Plugging in these values, we get:
\[ m = \frac{-6 - 6}{-9 - (-5)} \]
Calculating the numerator:
\[ -6 - 6 = -12 \]
Now calculating the denominator:
\[ -9 - (-5) = -9 + 5 = -4 \]
Now substituting back into the slope formula:
\[ m = \frac{-12}{-4} = 3 \]
Thus, the slope of the line that passes through the points \((-5, 6)\) and \((-9, -6)\) is \(\boxed{3}\).